2019
DOI: 10.1111/hel.12590
|View full text |Cite
|
Sign up to set email alerts
|

The eradication of Helicobacter pylori restores rather than disturbs the gastrointestinal microbiota in asymptomatic young adults

Abstract: Background The eradication of Helicobacter pylori (H pylori) has been suggested to reduce the risk of gastric cancer, but its impact on the gut microbiota has attracted public attention. This study aimed to investigate the short‐term and long‐term effects of bismuth quadruple therapy on both gastric and fecal microbiota. Methods Ten asymptomatic young adults with H pylori‐related gastritis were treated with bismuth quadruple therapy for 14 days, and 7 age‐matched adults without H pylori infection were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(134 citation statements)
references
References 40 publications
8
123
1
2
Order By: Relevance
“…23,47 Interestingly, recent report on the use of bismuth quadruple therapy indicates contradictory results, suggesting that H pylori eradication restores rather than disturbs the GIT microbiota by restoring the diversity of gastric microbiota with enrichment of beneficial bacteria, while other studies have shown alpha and beta diversity alterations. 45,48 As it is nowadays widely accepted that the gut microbiome is affected by a wide variety of factors, which includes physiological peculiarities of individual, BMI, gut-related and unrelated diseases, age, diet, and many other. Number of studies suggest that all these factors together mediate the unique composition of individual gut microbiome and our findings strongly support this by identifying "Individual" as major gut microbiome structure affecting factor in both main study groups.…”
Section: Influence Of Eradication Therapy On the Gut Microbiomementioning
confidence: 99%
“…23,47 Interestingly, recent report on the use of bismuth quadruple therapy indicates contradictory results, suggesting that H pylori eradication restores rather than disturbs the GIT microbiota by restoring the diversity of gastric microbiota with enrichment of beneficial bacteria, while other studies have shown alpha and beta diversity alterations. 45,48 As it is nowadays widely accepted that the gut microbiome is affected by a wide variety of factors, which includes physiological peculiarities of individual, BMI, gut-related and unrelated diseases, age, diet, and many other. Number of studies suggest that all these factors together mediate the unique composition of individual gut microbiome and our findings strongly support this by identifying "Individual" as major gut microbiome structure affecting factor in both main study groups.…”
Section: Influence Of Eradication Therapy On the Gut Microbiomementioning
confidence: 99%
“…Probiotic supplementation slightly counteracts the pervasive effects of antibiotics on the intestinal microbiota (defined by fluorescence in situ hybridization and culture) [108]. Long-lasting perturbations of specific taxa (often beneficial) were also reported in recent studies using meta-genomic and genomic analyses [111][112][113]. The potential for inducing persistent macrolide resistance in the nostrils, throat and fecal microbiota following eradication therapy has been also reported [109].…”
Section: Recommendation Grade: B; Evidence Level: 2c; Agreement Levelmentioning
confidence: 93%
“…Significant differences in microbial community structures were found between the H pylori ‐infected and negative control groups 33‐36 . The compositional analysis at the phylum level discovered that the abundance of Proteobacteria significantly increased in infected individuals, which could be due to the transfer of Helicobacter from the stomach to the intestinal lumen 6,34 . Of note, the Bacteroidetes:Firmicutes (B:F) ratio tended to be higher in the H pylori ‐positive group 6,31,37 .…”
Section: Gastrointestinal Microbiota Reshaping Upon H Pylori Infectionmentioning
confidence: 94%
“… 31,32 Strikingly, most studies investigating the relationship between H pylori infection and gut microbial diversity provided a positive correlation (Figure 2; Table 2). 31,33‐36 As higher microbial diversity is usually associated with an overall better health state, it will be interesting to explore whether the increased intestinal microbial diversity upon H pylori infection provides some beneficial effects to the host. Significant differences in microbial community structures were found between the H pylori ‐infected and negative control groups 33‐36 .…”
Section: Gastrointestinal Microbiota Reshaping Upon H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation